2023
DOI: 10.1186/s12936-023-04442-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax and SARS-CoV-2 co-infection in Venezuelan pregnant women: a case series

Abstract: Background Malaria‐endemic areas are not spared from the impact of coronavirus disease 2019 (COVID-19), leading to co-infection scenarios where overlapping symptoms impose serious diagnostic challenges. Current knowledge on Plasmodium spp. and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) co‐infection in pregnant women remains limited, especially in Latin America, where Plasmodium vivax infection is highly prevalent. Methods This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Studies have shown that the cases of co-infection of malaria and COVID-19 increased, and individuals with this co-infection may experience more severe symptoms and have a higher risk of complications. These risks are particularly concerning in regions where both diseases are endemic, as they can strain healthcare resources and lead to poorer patient service outcomes ( Alhaddad et al, 2023 ; Carrión-Nessi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the cases of co-infection of malaria and COVID-19 increased, and individuals with this co-infection may experience more severe symptoms and have a higher risk of complications. These risks are particularly concerning in regions where both diseases are endemic, as they can strain healthcare resources and lead to poorer patient service outcomes ( Alhaddad et al, 2023 ; Carrión-Nessi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%